Composite material, preparation method and application thereof, and preparation method of anticorrosive coating

By introducing a composite material of MIL-101(Fe) nano-containers and corrosion inhibitors into the coating, an anti-corrosion coating is formed, which solves the problem of poor self-healing effect and achieves efficient metal corrosion protection and good compatibility with oil-based coatings.

CN121406148APending Publication Date: 2026-01-27LIUYANG XIANGJIE MASCH MFG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511904484.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-17
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

The repair effect of existing self-healing coatings needs to be further improved. They cannot effectively block metal corrosion caused by humid air and have insufficient compatibility with oil-based coatings.

Method used

By using a composite material of MIL-101(Fe) nanocontainers and corrosion inhibitors, an anti-corrosion coating is formed by mixing and drying the nanocontainers in the coating. The nanocontainers release the corrosion inhibitors under humid conditions to achieve self-healing.

Benefits of technology

It achieves a highly efficient self-healing effect, protects metal materials for a long time, and is suitable for various oil-based coatings, especially effectively blocking metal corrosion under high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121406148A_ABST
    Figure CN121406148A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metal corrosion protection, and discloses a composite material, a preparation method and application thereof, and a preparation method of an anticorrosive coating. The invention relates to a composite material. The composite material comprises an MIL-101 (Fe) nano container and a corrosion inhibitor, wherein the average cavity diameter of the MIL-101 (Fe) nanometer container is 40 to 130 nm. An anti-corrosion coating prepared from the composite material is applied to metal corrosion protection and has an excellent self-repairing effect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of metal corrosion protection, in particular to a composite material and a preparation method and application thereof, and a preparation method of a corrosion-resistant coating. BACKGROUND

[0002] Metal materials are one of the most widely used materials in people's life, and are the main base materials for manufacturing high-strength security doors, modern ships, etc. Metal atoms have high degrees of freedom, and when the metal element is exposed to air, it is easy to react with oxygen or other oxidizing media in the air, which can cause corrosion. Metal corrosion often occurs under chemical reaction conditions, in addition to which, electrochemical reactions can also cause metal corrosion. Metal corrosion under chemical reaction is usually caused by the oxidation-reduction reaction between metal atoms and certain elements in the environment, such as the reaction between metal and oxygen in the air. Electrochemical corrosion is caused by the contact between metal and electrolyte during use, such as the occurrence of iron rust when carbon steel encounters water.

[0003] In order to inhibit the occurrence of metal corrosion, people have invented various metal corrosion protection strategies, mainly including various metal surface treatments and electrochemical protection methods. Among them, the coating protection method has a long application history in China and is one of the most widely used metal corrosion protection methods. The so-called coating protection method is to apply a layer of paint on the surface of the metal substrate to form a protective barrier. The coating protection method has multiple characteristics such as economy, convenience, effectiveness, etc. At the same time, in addition to effectively alleviating metal corrosion, the coating protection method is also more outstanding in terms of aesthetics, and is less likely to be limited by the size of the coating equipment, and the construction method is very simple. However, the coating is easily damaged by external forces during use, which exposes the metal material to the working environment and causes corrosion. Therefore, in recent years, various self-repairing coating technologies have emerged. According to the repair type, they are mainly divided into external aid type self-repairing coating and intrinsic type self-repairing coating. The external aid type self-repairing coating refers to the realization of self-repairing function by introducing external components such as microcapsules containing repair agent system, nano containers, microvessels or glass fibers into the coating matrix. This method needs to pre-embed various repair agent systems and then add them to the matrix; when the material is damaged, the repair agent in the damaged area is released under the action of external stimuli (force, pH value, temperature, etc.), thereby realizing self-repairing. Intrinsic self-repairing does not require an external repair system, but the coating material itself contains special chemical bonds or other physical and chemical properties such as reversible covalent bonds, non-covalent bonds, molecular diffusion, etc. to realize self-repairing function. SUMMARY

[0004] The present application aims at the problem that the repairing effect of the self-repairing coating used in the current metal corrosion protection needs to be further improved, and provides a composite material and a preparation method and application thereof, and a preparation method of a corrosion-resistant coating.

[0005] In order to achieve the above-mentioned purpose, the present application provides a composite material in the first aspect, which comprises MIL-101(Fe) nanocapsules and an inhibitor. The average cavity diameter of the MIL-101(Fe) nanocapsules is 40-130 nm.

[0006] The present application provides a preparation method of the composite material in the first aspect in the second aspect, which comprises mixing the MIL-101(Fe) nanocapsules and the inhibitor in the presence of a solvent, and then drying.

[0007] The present application provides an application of the composite material in the first aspect in the third aspect in the metal corrosion protection.

[0008] The present application provides a preparation method of a corrosion-resistant coating in the fourth aspect, which comprises mixing the composite material in the first aspect with a coating material.

[0009] Through the above technical solution, the present application has the following advantages: The composite material in the present application uses MIL-101(Fe) nanocapsules with a large cavity structure, which can ensure the stability of the nanocapsule structure while maximizing the inhibitor loading capacity of the nanocapsule. The corrosion-resistant coating prepared by using the composite material provided by the present application has the advantages of high repairing efficiency, long action time, simple use method, and low cost, and is suitable for various metal coatings, especially various oil-based coatings, and can realize long-term protection of metal materials.

[0010] The composite material in the present application has the characteristics of structural collapse under high humidity conditions through the synergistic effect of MIL-101(Fe) nanocapsules and an inhibitor, which effectively blocks the metal corrosion caused by humid air. The composite material in the present application can be compatible with most of the oil-based coatings on the market, and a corrosion-resistant coating can be prepared. When the corrosion-resistant coating is damaged, the composite material will be exposed, the MIL-101(Fe) nanocapsules of the composite material will absorb the moisture in the air, causing the collapse of the skeleton structure and releasing the inhibitor encapsulated therein, thereby quickly repairing the damaged part of the corrosion-resistant coating and protecting the base metal. BRIEF DESCRIPTION OF DRAWINGS

[0011] Figure 1This is a SEM image of the MIL-101(Fe) nanocontainer prepared in Example 1. Detailed Implementation

[0012] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0013] In one aspect, the present invention provides a composite material comprising a MIL-101(Fe) nanocontainer and a corrosion inhibitor; The average cavity diameter of the MIL-101(Fe) nanocontainer is 40-130 nm.

[0014] According to the present invention, the average cavity diameter of the MIL-101(Fe) nanocontainer is 40-130 nm, specifically 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, and any two of these values, preferably 100-130 nm. Controlling the cavity diameter of the MIL-101(Fe) nanocontainer within the above range is beneficial for achieving the optimal balance between the nanocontainer's loading capacity and material stability. Applying the anti-corrosion coating made from the composite material provided by the present invention to metal corrosion protection has the advantages of high repair efficiency and long service time. It is suitable for compatibility with various metal coatings, especially various oil-based coatings, and can achieve long-term protection of metal materials.

[0015] The average cavity diameter of the MIL-101(Fe) nanocontainer described in this invention was determined by measuring the adsorption / desorption isotherm of nitrogen on the material at liquid nitrogen temperature (-195.8℃) and analyzing the pore size distribution using the Barrett-Joyner-Halenda model.

[0016] According to the present invention, preferably, the average particle size of the MIL-101(Fe) nanocontainer is 110-220 nm, specifically it can be 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, 170 nm, 175 nm, 180 nm, 185 nm, 190 nm, 195 nm, 200 nm, 205 nm, 210 nm, 215 nm, 220 nm, and any two of these values, preferably 160-220 nm. Controlling the average particle size of the MIL-101(Fe) nanocontainer of the present invention within the above-mentioned preferred range is beneficial to improving the dispersibility of the subsequent composite material in coatings.

[0017] The average particle size of the MIL-101(Fe) nanocontainer described in this invention was measured by scanning electron microscopy (SEM).

[0018] According to the present invention, preferably, the mass ratio of MIL-101(Fe) nanocontainer to corrosion inhibitor is 1:1-3, specifically 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, and any two of these values ​​forming a range, preferably 1:1.5-3. Using this preferred embodiment, the resulting material exhibits optimal self-healing properties. When the mass ratio is below this range, the self-healing properties decrease. When the mass ratio is above this range, some corrosion inhibitor may leak prematurely.

[0019] In the composite material of the present invention, the mass ratio of MIL-101(Fe) nanocontainer to corrosion inhibitor is obtained by calculation of the feed amount.

[0020] According to the present invention, preferably, the corrosion inhibitor is selected from at least one of benzotriazole, 2-aniline-benzimidazole, and 2-toluene-benzimidazole, and more preferably from 2-aniline-benzimidazole and / or 2-toluene-benzimidazole. The present invention employs a specific preferred type of corrosion inhibitor, whose polar groups adsorb onto the metal surface, significantly increasing the activation energy of the metal ionization process; its non-polar groups are oriented on the metal surface, forming a hydrophobic film, which better hinders the diffusion of corrosion products, thereby inhibiting the corrosion reaction. Synergistically acting with the MIL-101(Fe) nanocontainer of the present invention, when applied to metal corrosion protection, it has the advantages of high repair efficiency and long action time.

[0021] According to the present invention, preferably, the corrosion inhibitor is encapsulated inside a MIL-101(Fe) nanocontainer.

[0022] According to the present invention, preferably, the method for preparing the MIL-101(Fe) nanocontainer includes: (1) In the presence of a solvent, the organic ligand, iron source and base source shown in Formula I are reacted to obtain a solid product; (2) Freeze-dry the solid product; Formula I.

[0023] The method for preparing the MIL-101(Fe) nanocontainer provided by this invention employs specific organic ligands, enabling the prepared MIL-101(Fe) nanocontainer to maintain MOF structural stability while possessing a large cavity structure. This ensures the nanocontainer has the maximum corrosion inhibitor loading capacity, and the resulting MIL-101(Fe) nanocontainer exhibits advantages such as humidity sensitivity. Subsequently, the corrosion inhibitor is encapsulated within the MIL-101(Fe) nanocontainer provided by this invention, resulting in a composite material that exhibits long-term self-healing properties at cracks, effectively preventing metal corrosion caused by humid air.

[0024] According to the present invention, preferably, the reaction conditions in step (1) include: a temperature of 90-120°C and a time of 10-36 h.

[0025] According to the present invention, preferably, the reaction in step (1) is carried out under stirring conditions.

[0026] The present invention does not impose any particular limitation on the stirring rate and time, which can be appropriately selected according to the specific circumstances, as long as the purpose of achieving a full reaction can be achieved.

[0027] According to one specific embodiment of the present invention, the reaction in step (1) is carried out under oil bath conditions.

[0028] The present invention does not have any particular limitation on the amount of the organic ligand and the iron source used, as long as the MIL-101(Fe) nanocontainer is obtained.

[0029] According to the present invention, preferably, in step (1), the mass ratio of the organic ligand to the iron source is 1:0.3-7, specifically 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, and any two of these values ​​forming a range. This preferred embodiment is advantageous in ensuring that the corrosion inhibitor in the subsequently prepared nanocontainer has the maximum loading capacity.

[0030] The reaction described in step (1) of this invention is carried out under alkaline conditions, which is beneficial to the good stability of the composite material prepared subsequently.

[0031] According to the present invention, preferably, in step (1), the mass ratio of the organic ligand to the alkali source is 1:0.2-0.6.

[0032] The present invention allows for a wide range of choices for the alkali source, which can be conventional choices in the art. The alkali source is an organic base and / or an inorganic base.

[0033] Preferably, the inorganic base is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0034] Preferably, the organic base is selected from at least one of dimethylamine, trimethylamine, diethylamine, triethylamine, diethanolamine, and triethanolamine.

[0035] The present invention allows for a wide range of solvent selection options in step (1), which can be conventional choices in the art. Preferably, in step (1), the solvent is N,N-dimethylformamide and / or N,N-diethylformamide.

[0036] The present invention does not have a particular limitation on the amount of solvent used, as long as the MIL-101(Fe) nanocontainer is obtained, it can be carried out according to conventional methods in the art.

[0037] The present invention has a wide range of choices for the type of iron source, which can be various iron sources commonly used in the field, as long as they contain iron, such as ferric chloride, ferric sulfate, etc.

[0038] This invention does not impose any particular limitation on the order in which the organic ligand, solvent, alkali source, and iron source are added in step (1). They can be added together or separately. To enhance the uniformity of mixing, it is preferable to first dissolve the organic ligand and alkali source in the solvent, and then add the iron source. In this invention, each material can be ultrasonicated or stirred after being added to achieve uniform mixing. This invention does not impose any particular limitation on this.

[0039] Preferably, the method further includes: performing solid-liquid separation on the reaction product of step (1) to obtain a solid product.

[0040] The present invention does not have any particular limitation on the solid-liquid separation, and conventional technical means in the field can be used. The present invention will not elaborate further here.

[0041] According to a specific embodiment of the present invention, the reaction product of step (1) is first cooled to room temperature, and then solid-liquid separation is performed.

[0042] According to the present invention, preferably, the freeze-drying conditions in step (2) include: a temperature of -10 to -50°C and a time of 180 to 300 min.

[0043] According to the present invention, preferably, the freeze-drying in step (2) is carried out under vacuum conditions.

[0044] Preferably, the preparation method of the MIL-101(Fe) nanocontainer further includes washing the solid product before freeze-drying it.

[0045] The present invention does not have any particular limitation on the washing method, and it can be carried out with reference to conventional methods in the art. In this invention, there is no particular limitation on the source of the organic ligand; it can be obtained commercially or prepared using conventional methods in the art. Conventional methods in the art can achieve the objective of this invention as long as an organic ligand having the formula shown in Formula I is obtained. This invention offers a wide range of methods for preparing the organic ligand. A specific method for preparing the organic ligand is provided here, but this invention is not limited thereto. Preferably, the method for preparing the organic ligand includes: S1. In the presence of a solvent, valeryl chloride, 2-aminoterephthalic acid and a base source are mixed to obtain a precipitate; S2. The precipitate is freeze-dried to obtain the organic ligand.

[0046] According to the present invention, preferably, the mixing conditions in S1 include: a temperature of 15-40°C and a time of 12-48h.

[0047] According to the present invention, preferably, in S1, the mass ratio of valeroyl chloride to 2-aminoterephthalic acid is 1:1-3.

[0048] The present invention allows for a wide range of solvent selection options in S1, which can be conventional choices in the art. Preferably, in S1, the solvent is acetone and / or diethyl ether.

[0049] The present invention does not have a particular limitation on the amount of solvent mentioned in S1. It can be appropriately selected according to the actual situation to achieve the purpose of dissolution.

[0050] The mixing described in S1 of this invention is carried out under alkaline conditions, which is beneficial for obtaining the organic ligands required by this invention.

[0051] The present invention allows for a wide range of choices for the alkali source described in S1, which can be conventional choices in the art. In S1, the alkali source is an organic base and / or an inorganic base.

[0052] Preferably, in S1, the alkali source is an organic alkali, preferably selected from at least one of dimethylamine, trimethylamine, diethylamine, triethylamine, diethanolamine, and triethanolamine.

[0053] Preferably, in S1, the inorganic base is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0054] Preferably, in S1, the mass ratio of valeryl chloride to the alkali source is 1:0.0001-0.03.

[0055] In the mixing process of the valeroyl chloride, 2-aminoterephthalic acid, solvent, and alkali source, there is no particular limitation on the order in which the materials are added; they can be added together or separately. To enhance the uniformity of mixing, it is preferable to add the valeroyl chloride and 2-aminoterephthalic acid first, then the solvent, and finally the alkali source.

[0056] In this invention, the materials can be ultrasonicated or stirred after addition to achieve uniform mixing. This invention does not impose any particular limitations on this process.

[0057] Preferably, in S2, the freeze-drying conditions include: a temperature of -10 to -50°C and a time of 180 to 300 minutes.

[0058] Preferably, in S2, the freeze-drying is carried out under vacuum conditions.

[0059] Preferably, in step S2, the precipitate is washed before freeze-drying.

[0060] The present invention does not impose any particular limitation on the washing conditions, which can be carried out in accordance with conventional methods in the art, and will not be described in detail here.

[0061] The present invention does not impose any particular limitation on the preparation method of the composite material, that is, the method of encapsulating the corrosion inhibitor in the MIL-101(Fe) nanocontainer is not particularly limited, and can be carried out with reference to conventional methods in the art.

[0062] A second aspect of the present invention provides a method for preparing the composite material described in the first aspect, the method comprising: mixing the MIL-101(Fe) nanocontainer and a corrosion inhibitor in the presence of a solvent, and then drying the mixture.

[0063] According to the present invention, preferably, in the method for preparing the composite material, the mixing is carried out under stirring conditions. The present invention does not particularly limit the stirring rate and time, and can appropriately select them according to specific circumstances, as long as sufficient mixing is achieved.

[0064] In the preparation method of the composite material described in this invention, there are no particular limitations on the specific drying conditions, which can be carried out according to conventional methods in the field, and will not be elaborated further here.

[0065] In the preparation method of the composite material of the present invention, the range of solvents that can be selected is relatively wide and can be conventional choices in the art. Preferably, in the preparation method of the composite material, the solvent is selected from at least one of acetone, diethyl ether, and petroleum ether.

[0066] In this invention, the order in which the materials are added during the mixing process of the MIL-101(Fe) nanocontainer, solvent, and corrosion inhibitor is not particularly limited; they can be added together or separately. To enhance mixing uniformity, it is preferable to add the solvent first, then the corrosion inhibitor, and finally the MIL-101(Fe) nanocontainer. In this invention, each material can be ultrasonicated or stirred after addition to achieve uniform mixing. This invention does not impose any particular limitations on this process.

[0067] The third aspect of this invention provides an application of the composite material described in the first aspect in metal corrosion protection.

[0068] According to the present invention, preferably, the composite material is used to prepare an anti-corrosion coating.

[0069] The fourth aspect of the present invention provides a method for preparing an anti-corrosion coating, wherein the composite material described in the first aspect is mixed with a coating to obtain an anti-corrosion coating.

[0070] The composite material described in this invention is compatible with most commercially available oil-based coatings. Preferably, the coating is an oil-based coating. The coating described in this invention can be any type of oil-based coating commonly found in the art. Preferably, the coating is selected from at least one of epoxy resin coatings, polyurethane coatings, and silicone coatings.

[0071] According to the present invention, preferably, the amount of composite material added is 10-100 g relative to 1 L of coating. Using this preferred embodiment, the anti-corrosion coating can maintain good physical properties and can quickly self-repair after being damaged.

[0072] The present invention will be described in detail below through embodiments.

[0073] The raw materials used in the following examples are all commercially available and of analytical grade.

[0074] Example 1 (1) Synthesis of organic ligands 8 g of valeryl chloride and 12 g of 2-aminoterephthalic acid were added to separate 1500 mL round-bottom flasks, followed by 1000 mL of acetone. The mixture was stirred at 1200 rpm for 30 min. Then, 10 mL of triethylamine was added, and the mixture was stirred at the same rate at 25 °C for 24 h to obtain a precipitate. The precipitate was washed with ethanol and then with deionized water, and then freeze-dried under vacuum at -15 °C for 4 h to obtain the organic ligand.

[0075] (2) Preparation of MIL-101(Fe) nanocontainers 200 mL of DMF was added to a 300 mL round-bottom flask, followed by 5.5 g of the organic ligand prepared in step (1) and 2 g of sodium hydroxide. Finally, 10 g of FeCl3·6H2O was added to obtain a mixture. The mixture was stirred at 1200 rpm for 5 min, then heated in an oil bath at 110 °C for 12 h, cooled to room temperature, and the solid product was separated. The solid product was washed with DMF and then with ethanol, and then freeze-dried at -30 °C under vacuum for 4 h to obtain MIL-101(Fe) nanocontainers. The specific parameters are shown in Table 1.

[0076] An example is given: a SEM image of the obtained MIL-101(Fe) nanocontainer, such as... Figure 1 As shown. (Through) Figure 1 As can be seen, the nanocontainer is a quasi-spherical particle with an average particle size of 188 nm, a rough surface, and contains a large number of pores.

[0077] (3) Preparation of composite materials 200 mL of anhydrous ethanol was added to a 300 mL round-bottom flask, followed by 6 g of 2-aniline-benzimidazole and 3 g of MIL-101(Fe) nanocontainers to obtain a mixture. The mixture was stirred for 5 min and then dried at 70 °C to obtain a composite material in which the corrosion inhibitor was loaded inside the MIL-101(Fe) nanocontainers.

[0078] Example 2 (1) Synthesis of organic ligands 8 g of valeryl chloride and 12 g of 2-aminoterephthalic acid were added to separate 1500 mL round-bottom flasks, followed by the addition of 1000 mL of acetone. The mixture was stirred at 1200 rpm for 30 min. Then, 10 mL of triethylamine was added, and the mixture was stirred at the same rate at 25 °C for 24 h to obtain a precipitate. The precipitate was washed first with ethanol, then with deionized water, and finally freeze-dried under vacuum at -30 °C for 4 h to obtain the organic ligand.

[0079] (2) Preparation of MIL-101(Fe) nanocontainers 200 mL of DMF was added to a 300 mL round-bottom flask, followed by 5.5 g of the organic ligand prepared in step (1) and 2 g of sodium hydroxide. Finally, 10 g of FeCl3·6H2O was added to obtain a mixture. The mixture was stirred at 1200 rpm for 5 min, then heated in an oil bath at 110 °C for 12 h, cooled to room temperature, and the solid product was separated. The solid product was washed with DMF and then with ethanol, and then freeze-dried at -30 °C under vacuum for 4 h to obtain MIL-101(Fe) nanocontainers. The specific parameters are shown in Table 1.

[0080] (3) Loading of corrosion inhibitor 200 mL of anhydrous ethanol was added to a 300 mL round-bottom flask, followed by 6 g of 2-toluene-benzimidazole and 3 g of MIL-101(Fe) nanocontainers to obtain a mixture. The mixture was stirred for 5 min and then dried at 70 °C to obtain a composite material in which the corrosion inhibitor was loaded inside the MIL-101(Fe) nanocontainers.

[0081] Example 3 The method of Example 1 was followed, except that the amount of organic ligand used was 3g and the amount of FeCl3·6H2O used was 15g, to obtain MIL-101(Fe) nanocontainers, the specific parameters of which are shown in Table 1.

[0082] The final product is a composite material.

[0083] Example 4 The method of Example 1 was followed, except that the amount of organic ligand used was 10g and the amount of FeCl3·6H2O used was 6g, to obtain MIL-101(Fe) nanocontainers, the specific parameters of which are shown in Table 1.

[0084] The final product is a composite material.

[0085] Example 5 The method of Example 1 was followed, except that 2-amino-terephthalic acid was used as the organic ligand to obtain MIL-101(Fe) nanocontainers, the specific parameters of which are shown in Table 1.

[0086] The final product is a composite material.

[0087]

[0088] As shown in Table 1, the MIL-101(Fe) nanocontainer described in this invention has a large cavity structure. The composite material prepared using the MIL-101(Fe) nanocontainer with its large cavity structure ensures the structural stability of the nanocontainer while maximizing its corrosion inhibitor loading. Applying the anti-corrosion coating prepared using the composite material provided by this invention to metal corrosion protection offers advantages such as high repair efficiency and long-lasting action. It is suitable for use with various metal coatings, especially various oil-based coatings, enabling long-term protection of metal materials.

[0089] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A composite material, characterized in that, The composite material includes a MIL-101(Fe) nanocontainer and a corrosion inhibitor; The average cavity diameter of the MIL-101(Fe) nanocontainer is 40-130 nm.

2. The composite material according to claim 1, wherein, The average cavity diameter of the MIL-101(Fe) nanocontainer is 100-130 nm; Preferably, the average particle size of the MIL-101(Fe) nanocontainer is 110-220 nm, and more preferably 160-220 nm.

3. The composite material according to claim 1, wherein, The mass ratio of MIL-101(Fe) nanocontainer to corrosion inhibitor is 1:1-3; Preferably, the corrosion inhibitor is selected from at least one of benzotriazole, 2-aniline-benzimidazole and 2-toluene-benzimidazole, more preferably selected from 2-aniline-benzimidazole and / or 2-toluene-benzimidazole; Preferably, the corrosion inhibitor is encapsulated inside a MIL-101(Fe) nanocontainer.

4. The composite material according to any one of claims 1-3, wherein, The preparation method of the MIL-101(Fe) nanocontainer includes: (1) In the presence of a solvent, the organic ligand, iron source and base source shown in Formula I are reacted to obtain a solid product; (2) The solid product is freeze-dried; Formula I.

5. The composite material according to claim 4, wherein, The reaction conditions in step (1) include: a temperature of 90-120℃ and a time of 10-36 h; Preferably, in step (1), the mass ratio of the organic ligand to the iron source is 1:0.3-7; Preferably, in step (1), the mass ratio of the organic ligand to the alkali source is 1:0.2-0.

6.

6. The composite material according to claim 4, wherein, The freeze-drying conditions described in step (2) include: a temperature of -10 to -50°C; and a time of 180 to 300 min. Preferably, the freeze-drying in step (2) is carried out under vacuum conditions.

7. A method for preparing the composite material according to any one of claims 1-6, the method comprising: The MIL-101(Fe) nanocontainer and corrosion inhibitor were mixed in the presence of a solvent and then dried.

8. The application of the composite material according to any one of claims 1-6 in metal corrosion protection; Preferably, the composite material is used to prepare an anti-corrosion coating.

9. A method for preparing an anti-corrosion coating, characterized in that, The method includes mixing the composite material according to any one of claims 1-6 with a coating.

10. The preparation method according to claim 9, wherein, The coating is an oil-based coating, preferably selected from at least one of epoxy resin coatings, polyurethane coatings, and silicone coatings; Preferably, the amount of composite material added is 10-100 g relative to 1 L of coating.